Nickel on two-dimensional ITQ-2 zeolite as a highly active catalyst for carbon dioxide reforming of methane. (April 2022) - Kweon, Sungjoon; Kim, Young Woo; Bae, Jongil; Kim, Eun-Jeong; Park, Min Bum; Min, Hyung-Ki
Abstract: The physicochemical properties of the support material are important parameters that determine the activity and stability of supported metal catalysts in chemical reactions. In this study, we investigated the influence of the support dimensionality and nickel loading (5, 15, and 30 wt%) of supported-Ni catalysts for the carbon dioxide reforming of methane (CDR) by comparing the three-dimensional (3D) Ni/MCM-22 and its delaminated two-dimensional (2D) Ni/ITQ-2 catalyst. Owing to its delaminated nature, Ni/ITQ-2 exhibited a large external surface area (319 m 2 g −1 ) and a high proportion of the nickel phyllosilicate phase, even for 30 wt% Ni loading. In addition, the strong interaction of Ni clusters with phyllosilicate resulted in a high dispersion of Ni. The 2D Ni/ITQ-2 catalysts generally exhibited a higher catalytic performance than the 3D Ni/MCM-22 catalysts. The relative proportion of the nickel phyllosilicate phase in the catalyst also played a promoting role in achieving a high catalytic performance for CDR. Unlike Ni/ γ -Al2 O3, Ni/ITQ-2 exhibited high conversions of CH4 and CO2, regardless of pre-reduction, which is advantageous for catalyst handling. Graphical Abstract: ga1 Highlights: Ni catalysts loaded on two-dimensional support with large external surface area. Comparison of two- and three-dimensional zeolites as support materials. Highly active and stable Ni catalyst achieved for CO2 reforming of CH4. Strong metal-support interaction between Ni species and phyllosilicate phase.